Black Carbon Concentration during Spring Season at High Altitude Urban Center in Eastern Himalayan Region of India - Khushboo Sharma; Rakesh Kumar Ranjan; Sargam Lohar; Jayant Sharma; Rajeev Rajak; Aparna Gupta; Amit Prakash; Alok Kumar Pandey (Asian Journal of Atmospheric Environment, 2023)
Abstract This study analyzed the BC associated with PM1 and the contribution of biomass burning to the BC using a portable seven-channel Dual spot Aethalometer in and around Gangtok, the capital city of Sikkim, India, during April 2021. Additionally, CO2 and meteorological parameters (Temperature, Pressure, and Relative Humidity) was measured. The minimum concentration of BC was found in rural areas where the contribution of biomass burning to the BC is highest. The observed spatial variability of BC over Gangtok Municipal Corporation (GMC) area is minimal. Five days back-trajectory analysis was done using the Hybrid Single Particle Lagrangian Integrated Trajectory (HYSPLIT) model to understand the regional influences of air masses at Gangtok. The air mass of the studied region is under influence of trans-regional transport from Indo-Gangetic Plains affecting the BC concentration over the studied region. The black carbon presence in the ambient air near the glacier heights in the Eastern Himalayan region may significantly cause localized warming, thereby enhancing glacier melts. The results have significant bearing for the policy-makers to take corrective steps in addressing the issue of rising BC concentration in high altitude regions. A further detailed study is needed to examine the effect of BC on radiative forcing and its large-scale effect on the East Asian summer monsoon using regional climate models.